General variational inclusions in Lp spaces - Muhammad Aslam Noor (International Journal of Mathematics and Mathematical Sciences)
It is well known that the variational inclusions are equivalent to the fixed point problems. We use this equivalent alternative formulation to suggest and analyze some iterative methods for solving variational inclusions in Lp spaces. We also consider the convergence analysis of these new iterative methods under some suitable conditions.